2017
DOI: 10.1016/j.jssc.2016.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Structural, photoluminescence and radioluminescence properties of Eu3+ doped La2Hf2O7 nanoparticles

Abstract: This study presents the structural, optical, and radioluminescent characterization of newly synthesized europium-doped lanthanum hafnate (La 2 Hf 2 O 7 :xmol%Eu 3+ , x = 0 to 35) nanoparticles (NPs) for use as phosphors and scintillation materials. Samples prepared through a combined co-precipitation and molten salt synthetic process were found to crystalize in the pyrochlore phase, a radiation tolerant structure related to the fluorite structure. These samples exhibit red luminescence under ultraviolet and X-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
49
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(53 citation statements)
references
References 54 publications
1
49
0
3
Order By: Relevance
“…While the aforementioned principles still apply, nanoparticle scintillators have their own sets of rules for synthesis and luminescent properties. Nanomaterials have expanded the possibilities for X-ray luminescence uses in high-energy physics and medical imaging, providing a large portfolio of compositions including composite films, vitroceramics, thin films, coordination compounds, metal-organic frameworks (MOFs), and organic-inorganic hybrid materials (Cooper, Bekah, & Nadeau, 2014;Hamieh, Dorkenoo, Taupier, Henry, & Halley, 2017;Pereira, Martin, Levinta, & Dujardin, 2015;Vistovskyy et al, 2014;Vistovskyy et al, 2016;Wahid, Pokhrel, & Mao, 2017). Even pure metals and semiconductors, which usually do not function as X-ray scintillators, may function as such if formed into nanoparticles (Brus, 1984;Paillard et al, 1999;Yuan et al, 2013).…”
Section: This Article Is Categorized Undermentioning
confidence: 99%
“…While the aforementioned principles still apply, nanoparticle scintillators have their own sets of rules for synthesis and luminescent properties. Nanomaterials have expanded the possibilities for X-ray luminescence uses in high-energy physics and medical imaging, providing a large portfolio of compositions including composite films, vitroceramics, thin films, coordination compounds, metal-organic frameworks (MOFs), and organic-inorganic hybrid materials (Cooper, Bekah, & Nadeau, 2014;Hamieh, Dorkenoo, Taupier, Henry, & Halley, 2017;Pereira, Martin, Levinta, & Dujardin, 2015;Vistovskyy et al, 2014;Vistovskyy et al, 2016;Wahid, Pokhrel, & Mao, 2017). Even pure metals and semiconductors, which usually do not function as X-ray scintillators, may function as such if formed into nanoparticles (Brus, 1984;Paillard et al, 1999;Yuan et al, 2013).…”
Section: This Article Is Categorized Undermentioning
confidence: 99%
“…These properties make them suitable for scientific and technological applications such as thermal barrier coatings, magnetic materials, electrocatalysis, sensors, optical materials, solid‐oxide fuel cells, high level nuclear waste hosts, etc. Moreover, recently relevant nanostructured pyrochlore materials have gained significant attention compared with their bulk counterparts in the areas of photoluminescence, scintillation, and magnetism …”
Section: Introductionmentioning
confidence: 99%
“…Recent studies on zirconate based phosphors show that, Zr 4+ exists in d 0 configuration play a very decisive role in ligand to metal charge transfer (LMCT) . There are only a few independent reports on the luminescence studies of La 2 X 2 O 7 :Eu 3+ (X = Zr and Hf), but comparative studies for the observed differences are missing, not to mention the understanding of the underlying mechanisms both experimentally and theoretically, including the energetics of ionized oxygen vacancies, the host to dopant energy transfer, and non‐radiative channels …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations